AROUSING STUDENTS’ PATRIOTISM BY ASSESSING THE SPEAKING MATERIALS THROUGH SCAS MODEL - Hayati Syafri; Sendu Ardila (English Language Teaching and Research, 2017)
Nowadays, the patriotism in the students’ life has started to vanish. Futhermore, some experts say that it happens because of the influence of globalization that detract their identities and love to their country. Besides, there are many students who idolized the figures out of their country. Sadly, they do not attentive with their local prominent figures who have amazing character, good morality and many accomplishment. Due to the degragation and scraping the patriotism of the students, the writers did the materials development for students in IAIN Bukittinggi by using the PIE (Planning, Implementing and Evaluating) to insert the biography of the  prominent figures in the  speaking material. It is supported by Socio-Cultural Affective Strategies (SCAS) model which considering the social, affective, and culture with multi-dimensional of speaking material by the used of video call with native speaker that can influence patriotism of the students. From that SCAS model, the researchers do assessing to see how far the modul gives the contribution to improve students patriotism. Briefly, this developing material effectively help the students to counteract them from indeterminate as the effect of globalization that furnish the insight of the students about interculturality. Keywords: Assessing Speaking Materials, SCAS-Model